4th International congress on science and skiing, December 14-20, 2007, St. Christoph am Arlberg - Austria. Books of Abstracts. (University of Salzburg, 2007)
Abstractband der Beiträge des 4. Internationalen Kongresses "Wissenschaft und Skisport" vom 14.-20. Dezember 2007 in Salzburg, Österreich (je eine Seite pro Beitrag).